A qualidade do vínculo como ponto de partida para o manejo de conflitos trabalhistas - João Pedro de Rezende Martins (2022)
This study seeks to bring the psychosocial and legal views closer to the concept of bond, intending to build less explored understandings about the reasons that could lead the Labor Court to be the preferred option of employees for the resolution of conflicts arising from a work relationship. It proposes the idea that the perception, by the subjects, of their affective experience in the bond caused by a work relationship, referred to as bond quality, influences their availability for the development of a negotiated solution. And when associated with the perception of an imbalance of power, the tendency of the party that considers itself less favored points to the need for legal certainty, with the resulting preference for the judicialization of the conflict. It is proposed to understand work relationships as human relationships, investigating how bonds are created from agreements and conflicts that structure the space between subjects, suggesting that individual perception of this intersubjective environment guides the behavior of subjects in the face of conflicts of work. In this trajectory, legal and psychological concepts around the ideas of bonds, human relations and legal relations are revisited to understand labor conflicts in their wide diversity, paying attention to the invariable human characteristics present in all bonds. Finally, a constructive criticism is developed regarding the usual judicial or extrajudicial referrals and concluding that the evaluation of the subjective perception of the quality of the bond, from the proposed criteria - referred to as recognition, perspective, environment and reward – offers original and consistent starting points for a deeper understanding of conflicts in labor relations in their most human aspects, indicating common characteristics and points of attention for the construction of a new agreement as a solution.